Advancing Educators: Exploring Innovative Strategies For Teacher Training in Pakistan - Zohaib Hassan Sain; Chanda Chansa Thelma; Nurulannisa Binti Abdullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the barriers hindering practical teacher training in Pakistan and proposes actionable solutions to these challenges. The study builds a robust foundation by examining existing research within the Pakistani educational landscape, national education policies, and relevant academic literature. Analysis of secondary data highlights various issues in teacher training in Pakistan, spanning administrative and faculty-related dimensions. Critical problems identified include flaws in policy and planning, substandard teacher induction processes, insufficient resources in training institutions, low teacher motivation, imbalanced distribution of qualified teachers, a fragmented training system, and infrequent training sessions. To address these challenges, the study recommends fostering a supportive environment, ensuring accountability and merit-based practices, allocating adequate resources, designing comprehensive professional development programs, and maintaining continuity. In conclusion, addressing challenges like poor induction, inadequate training, and lack of resources is essential for improving teacher training in Pakistan, which is crucial for enhancing the overall quality of education.